The Disability Creation Process Model: A Comprehensive Explanation of Disabling Situations as a Guide to Developing Policy and Service Programs - Patrick Fougeyrollas; Normand Boucher; Geoffrey Edwards; Yan Grenier; Luc Noreau (Scandinavian Journal of Disability Research, 2019)
Understanding disability remains a challenge. Although the international community has largely embraced the idea that disability is the product of social and environmental practices, society still lacks good conceptual frameworks. In an era when the rights of persons with disabilities have been enshrined in international and national laws, such frameworks have become a necessity. Within the province of Quebec, Canada, the Disability Creation Process (DCP) model has served such a role. Furthermore, recent efforts to enrich the model enhance the applicability of this powerful tool to a broader range of contexts. As a result, the DCP model could be used more widely than it is today. In this paper we provide the foundations of the approach encapsulated by the model and explain how its usage guides policy development and service delivery within the province of Quebec. We also highlight its forward-looking capacities.